ТӘЛИМДЕ ИННОВАЦИЯНЫҢ ҲӘМ ИНТЕГРАЦИЯНЫҢ ӘҲМИЙЕТИ - Сайтбекова, С.; Уснатдинова, Н. (ILIM hám JÁMIYET, 2019)
In the article the author considers the importance of the integration of preprimary and primary education, using innovations and ped- agogical technologies for improvement of the quality of education.